A Shot at a Healthy Future - Nielsen, Stine Hauberg; Andersen, Rikke Sand; Tørring, Marie Louise (Tidsskrift for Forskning i Sygdom og Samfund, 2020)
In this article, we present an extended case analysis of the unruly reception of the HPV vaccine in Denmark. More specifically, we explore what happens to visions of a healthy future when high levels of social trust in a public vaccination programme are suddenly infused with uncertainty and doubt. Capturing the Danish public in 2013-2015, national news and social media platforms shared dra-matic stories of young women confined to their beds following their HPV vaccinations. The Danish healthcare authorities reacted to this seemingly accelerating problem by setting up HPV clinics to care for the women. Simultaneously, HPV vaccination uptake plunged. Based on long-term ethno-graphic field research, we present the experiences of two main interlocutors, who both find them-selves in difficult situations and having to revise their visions of the future: Sophie, a young woman with suspected HPV vaccine side effects and Martin, a physician working in an HPV clinic. Overall, their accounts shed light on situations emerging during a challenging period in the 2010s in which the Danish healthcare system was adjusting to a new information and media landscape. We show that the promise of a healthy future – sustained by welfare and vaccine technologies – is indeed a communal venture that is vulnerable to suspension and even collapse. When sufferings (such as pain or fatigue) were publicly paired and un-paired with the vaccine, it generated and sustained pervasive uncertainties and painful feelings of being doubted by others – reflecting and highlighting inherent tensions of preventative medicine and the Danish welfare society, including the subtle acts of power and resistance that occur within it.